POLA PENYEBARAN KANTONG SEMAR (Nepenthes spp.) DI KAWASAN GUNUNG SELINDUNG DESA TWI MENTIBAR KECAMATAN SELAKAU KABUPATEN SAMBAS - Hagga, Arinsl; Herawatiningsih, Ratna; AM, Iskandar (JURNAL HUTAN LESTARI, 2018)
The Nepenthes is the herb and it can grow as liana or terrestrial. Community activities and dependence on the natural resources has its negative impact on the preservation of biodiversity and ecosystem. This study aim was to examine the dispersion pattern of nepenthes. The reseach used survey method with double plots technic give size of the plot 5 m x 5 m. Several data analyzes were applied on this research such as density, frequency, importance value index and Morisita Index. The results signify 3 species of Nepenthes, they are N. Reinwardtiana Miq, N. Mirabilis Druce and N. ampullaria Jack with a total number of individual nepenthes is 1.039, the southern part has 486 individual species of N. mirabilis Druce with clumped dispersion pattern. There are 17 individual species of N. mirabilis Druce (Uniform) and 102 individual species of N. reinwardtiana Miq with clumped dispersion pattern in the western part, there are 23 individual species of N. ampullaria Jack with clumped dispersion pattern in the eastern part, and 411 individual species of N. reinwardtiana Miq with clumped dispersion pattern. While in thes northern part, there was no Nepenthes found as the place is covered tightly by the canopy, sunlight is blocked. 1039 individual species of Nepenthes with clumped dispersion pettern found at the compass points (south, east, west) in order to achieve the sustainability and the ecosystem balance, therefore, it is expected thet the relevant agencies will give extra attention to the area.Keyword: Dispersion Pattern, Double Plots, Mirabilis Druce, Nepenthes spp, Selindung Mounth